A Review On The Used Of Bamboo As Aggregate In Concrete With Different Type Of Treatment - Idris, Nur'ain; Mohd Noh, Hamidun; Md Zor, Muhammad Fahmi; Abdul Wahab, Nur Shazrina (Multidisciplinary Applied Research and Innovation, 2021)
The exploring of this study was collected from the previous research that focused on bamboo that sensitive with moisture depending on its environment. The treatment of bamboo before being aggregated are given priority. Methodology of study was descriptive and qualitative which include review of literature on properties, proportion, design and treatment of bamboo. From the result it is conclude that there are some properties of bamboo that help to strengthen the concrete. However, the problem can be overcome by treating the bamboo before mixing it in the concrete. Epoxy is found as a suitable treatment for bamboo and the design of the bamboo into pieces with a cut size of 2 to 4 cm length, 1 to 2 cm breadth and 1 cm thickness lead to good results. After analyzed all of the result, the best percentage of bamboo to be added into the concrete was between 5 -15 percent.The exploring of this study was collected from the previous research that focused on bamboo that sensitive with moisture depending on its environment. The treatment of bamboo before being aggregated are given priority. Methodology of study was descriptive and qualitative which include review of literature on properties, proportion, design and treatment of bamboo. From the result it is conclude that there are some properties of bamboo that help to strengthen the concrete. However, the problem can be overcome by treating the bamboo before mixing it in the concrete. Epoxy is found as a suitable treatment for bamboo and the design of the bamboo into pieces with a cut size of 2 to 4 cm length, 1 to 2 cm breadth and 1 cm thickness lead to good results. After analyzed all of the result, the best percentage of bamboo to be added into the concrete was between 5 -15 percent.